Retardan Variation of Paclobutrazol in VW (Vacin & Went) Media Towards the Artificial seeds Viability of the Dendrobium sp. - Elimasni (Talenta Publisher, 2022)
The research of the variation of paclobutrazol retardant in VW (Vacin & Went) media toward the viability of artificial seeds of Dendrobium sp. had been carried out at the Laboratory of Physiology and Plant Tissue Culture, Department of Biology, Faculty of Mathematics and Natural Sciences, University of North Sumatra, Medan. The purpose of the study was to obtain the best combination of paclobutrazol treatments and the storage time on the viability of artificial seeds of Dendrobium sp. This study used a factorial completely randomized design by two factors, which were six levels of paclobutrazol 0; 1; 2; 3; 4; 5 ppm, and 2 levels of storage duration times (0; 2; 4 weeks). The statistical analysis of the data showed that the combination of paclobutrazol treatments and storage times significantly affected the growth time of plb Dendrobium sp. as well as the wet weight and the dry weight (P < 0.05). Paclobutrazol concentration of 4 ppm and storage period of 4 weeks (P4L2) gave the best effect in delaying the growth of synthetic seeds of Dendrobium sp. with an average growth of 21.6 days. The 2 ppm treatment of paclobutrazol and the 4 weeks storage time (P2L2) gave the highest wet weight and dry weight by an average of 0.198 grams and 0.007760 grams, respectively.